(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This paper examines the role of fiscal measures in promoting economic development during India’s post-pandemic recovery. Using secondary data from 2016 to 2020, the study focused on fiscal deficit trends, stimulus measures, sectoral GDP, and employment implications—with an emphasis on debt policy dynamics and their relationship to economic recovery in the wake of the COVID-19 pandemic. These results support a strong inverse relationship between rates of growth of fiscal deficit rates and growth rates: For example, high deficits contract these growth rates through their contractionary effects, which lower fiscal flexibility and increase debt service cost. At the same time, the data showed that the greatest contribution to GDP growth would come from improved infrastructure as well as increases in liquidity. The report also said targeted budgetary measures were even more important for manufacturing and services sectors, which bore the brunt of job losses brought by the pandemic. Foreign debt risk was also increased at the expense of fiscal flexibility, along with domestic debt massively increased. The research above indicates the extent to which India’s short run fiscal response to the pandemic was successful towards (inclusive growth, sectoral interventions, and sustainable fiscal policy) and long term growth in India. This study contributes to closing an important research gap on how many fiscal policies are capable of meaningfully supporting a post pandemic economic recovery, and what policy implications of fiscal development plans are necessary for enhancing their sustainability